Features of medical image processing - Nosova, Ya. V.; Tymkovych, M. Y.; Kovalova, A. A.; Jiao, Hankun; Shushliapina, N. O. (My University, 2019)
Features of medical image processing are described
Keywords: medical image processing; visualization; segmentation; preprocessing